(untitled) (Conference on English Language Teaching, 2023)
Traditionally, the teacher was the main informant and the only lecturer in the classroom, but with the shift to the learner-centered paradigm, things changed, and learners take their responsibility to enhance their own different skills with a small guidance from their teacher. Recently, the teaching-learning process has witnessed an increasing use of information and communication technologies (ICTs) which are always developed and changed throughout history and all over the world. The ICT platform is used in this study, namely: Google Docs and Meet as a tool to teach reading comprehension at UIN Raden Mas Said Surakarta. In this regard, this study aims at inspecting the students’ perceptions regarding the use of Google Docs and Meet in teaching reading. The study was descriptive qualitative study whose subjects were sixty seven (67) second semester students from English Education Study Program at UIN Raden Mas Said Surakarta. Based on the data collected through questionnaires and interviews, there were various points concluded like: the using google docs and meets help learners to improve their reading ability, which facilitates reading activities. In addition, students observed that using visual aids increases students’ excitement and motivation towards reading and the course becomes more interesting and creative. Moreover, students faced problems while using Google Docs and Meet like the lack of computers and infrastructure. Accordingly, the study concludes that the use of Google Docs and Meet enable students to engage easily with reading texts and make interaction with other students when discussing the reading texts. Therefore, this study proclaims that teachers should try to create new ways to use Google Docs and Meet while teaching reading as much as possible